Two thumb compared with two finger cardiopulmonary resuscitation in infants. Issue 6 (20th October 2004) - Martin, Bruce; Butler, John
Abstract : A short cut review was carried out to establish whether the two thumb technique was superior to the two finger technique in delivering effective chest compressions in infants with cardiac arrest. Altogether 175 papers were found using the reported search, of which four presented the best evidence to answer the clinical question. The author, date and country of publication, patient group studied, study type, relevant outcomes, results and study weaknesses of these best papers are tabulated. A clinical bottom line is stated.